MIDAS (Migraine Disability Assessment): a valuable tool for work-site identification of migraine in workers in Brazil - Fragoso, Yara Dadalti (São Paulo Medical Journal, 2002)
CONTEXT: MIDAS was developed as a fast and efficient method for identification of migraine in need of medical evaluation and treatment. It was necessary to translate MIDAS, originally written in English, so as to apply it in Brazil and make it usable by individuals from a variety of social-economiccultural backgrounds. OBJECTIVE: To translate and to apply MIDAS in Brazil. SETTING: Assessment of a sample of workers regularly employed by an oil refinery. SETTING: Refinaria Presidente Bernardes, Cubatão, São Paulo, Brazil. PARTICIPANTS: 404 workers of the company who correctly answered a questionnaire for the identification and evaluation of headache. When the individual considered it to be pertinent to his own needs, there was the option to answer MIDAS as well. METHODS: MIDAS, originally written in English, was translated into Brazilian Portuguese by a neurologist and by a translator specializing in medical texts. The final version of the translation was obtained when, for ten patients to whom it was applied, the text seemed clear and the results were consistent over three sessions. MAIN MEASUREMENTS: Prevalence and types of primary headaches, evaluation of MIDAS as a tool for identification of more severe cases. RESULTS: From the total of 419 questionnaires given to the employees, 404 were returned correctly completed. From these, 160 persons were identified as presenting headaches, 44 of whom considered it worthwhile answering MIDAS. Nine of these individuals who answered MIDAS were identified as severe cases of migraine due to disability caused by the condition. An interview on a later date confirmed these results. Three were cases of chronic daily headache (transformed migraine) and six were cases of migraine. CONCLUSIONS: MIDAS translated to Brazilian Portuguese was a useful tool for identifying severe cases of migraine and of transformed migraine in a working environment. The workers did not consider MIDAS to be difficult to answer. Their high level of voluntary participation demonstrates that this medical condition was of real interest among the workers, whether they were sufferers or not.